2012
DOI: 10.1186/1742-6405-9-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Subtype distribution in morocco based on national sentinel surveillance data 2004-2005

Abstract: BackgroundLittle is known about HIV-1 subtype distribution in Morocco. Some data suggest an emergence of new HIV subtypes. We conducted phylogenetic analysis on a nationally representative sample of 60 HIV-1 viral specimens collected during 2004-2005 through the Morocco national HIV sentinel surveillance survey.ResultsWhile subtype B is still the most prevalent, 23.3% of samples represented non-B subtypes, the majority of which were classified as CRF02_AG (15%). Molecular clock analysis confirmed that the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…41 Nevertheless, recent data suggest increasing diversity of strains with over 25% of the infections being of non-B subtypes, including several circulating recombinant forms. 42 45 A recent phylogenetic analysis showed that 39% of the recombinant strains (CRF02_AG) were closely connected with reference strains from Morocco, and 61% clustered with reference strains from eight West African and three European countries. 44…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…41 Nevertheless, recent data suggest increasing diversity of strains with over 25% of the infections being of non-B subtypes, including several circulating recombinant forms. 42 45 A recent phylogenetic analysis showed that 39% of the recombinant strains (CRF02_AG) were closely connected with reference strains from Morocco, and 61% clustered with reference strains from eight West African and three European countries. 44…”
Section: Resultsmentioning
confidence: 99%
“…The dominant HIV strain in Morocco is subtype B reflecting transmission pathways of West European origins and affirming the introduction of the virus to Morocco through the sizable migration and tourism links between this country and West Europe. 41,45,46 However, recent data indicate increasing diversity of HIV-1 variants reflecting sub-Saharan African immigration to Europe via Morocco or possibly acquisitions by Moroccans traveling in sub-Saharan Africa. 41 45 However, the Africanization of subtypes, that is, the increased appearance in Morocco of subtypes circulating in sub-Saharan Africa, should not be interpreted as a major role for African migrants in HIV transmission dynamics in Morocco.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 51 CRFs have been identified [10] with a significant proportion presently found in Africa alongside all the other groups and subtypes [7]. Subtype C has continued to predominate in the Southern parts of Africa (South Africa, Zambia and Zimbabwe) [9] while subtype B is seemingly the most common in North Africa (Morocco, Egypt, Algeria) [1113]. West and Central African countries have a wide distribution of HIV-1 M subtypes and Cameroon probably harbours the highest number of HIV-1 subtypes [10].…”
Section: Introductionmentioning
confidence: 99%
“…The possible inter-subtype recombination was analyzed with the Recombination Identification Program (RIP). 3 Molecular transmission clusters (MTCs) were defined as clusters with 2 or more sequences having bootstrap support greater than 80% (the criterion for phylogenetic confidence) and a pairwise gene distance less than or equal to 0.03 (the pairwise gene distance was calculated using the Tamura–Nei parameter model and setting the bootstrap to 1,000 with MEGA 7.0) ( 25 27 ).…”
Section: Methodsmentioning
confidence: 99%